Penerapan Budgeting dalam Meningkatkan Usaha Kecil - Nisrina, Ulfah Laila (Jurnal Ilmiah Manajemen & Kewirausahaan, 2025)
This study aims to explore the implementation of budgeting in improving the performance and sustainability of small businesses. A qualitative descriptive approach was employed to gain an in-depth understanding of how small business owners plan, apply, and perceive budgeting practices in their daily business activities. Data were collected through in-depth interviews and observations involving small business actors who actively manage their own finances. The findings indicate that budgeting helps small business owners control expenses, plan business activities more systematically, and make better financial decisions. However, the study also reveals that budgeting is often applied in a simple and informal manner, influenced by limited financial knowledge, experience, and business scale. Despite these limitations, budgeting is perceived as a useful tool that supports business stability and gradual growth. This study concludes that effective budgeting practices, even when implemented in a simple form, play an important role in improving the management and continuity of small businesses, highlighting the need for financial literacy support and practical guidance tailored to small business contexts.